Structural peculiarities of quench-condensed pure and argon-doped nitrous oxide: Low-Temperature Thermodynamics and Structure - Solodovnik, A.A.; Danchuk, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Electron diffraction studies have been carried out for condensed N2O and N2O–Ar films. Depositiontook place at substrate temperatures of 10 and 20 K. The growth process of N2O deposits was studied. A strong effect of argon impurities on the structure of the nitrous oxide matrix has been observed. The phase separation of the solutions was studied. The equilibrium solubility of argon atoms in nitrous oxide is very low. Introduction of a small amount of argon impurity into the molecular lattice destroyed the crystal structure. An effect of the size of the sample on its structure was also studied.